2014
DOI: 10.1021/jp503541n
|View full text |Cite
|
Sign up to set email alerts
|

Initial Stages of Oxygen Chemisorption on the Ge(001) Surface

Abstract: There is currently considerable interest in processes associated with the modification of germanium surfaces due to their potential application in electronic components such as MOSFETs. In this work, we combine first-principles total energy and reaction path calculations to study the initial stages of the oxidation of the Ge(001) surface due to the adsorption of both atomic and molecular oxygen. The obtained results provide real insights regarding several outstanding issues in the literature, including the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
(96 reference statements)
3
9
0
Order By: Relevance
“…The preferential inclination of the O 2 molecules onto the up-dimer Ge atoms is certainly not found in the silicon counterpart and the previous reports of the chemically treated Ge surfaces [33,34,36,37]. On the one hand, the non-dissociative model should be forsaken, because it would result in only one GeO and one O 1s component.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The preferential inclination of the O 2 molecules onto the up-dimer Ge atoms is certainly not found in the silicon counterpart and the previous reports of the chemically treated Ge surfaces [33,34,36,37]. On the one hand, the non-dissociative model should be forsaken, because it would result in only one GeO and one O 1s component.…”
Section: Resultsmentioning
confidence: 75%
“…The established records of initial O 2 adsorption on Ge(001) have made their comments based on the very first work by Fukuda and Ogina two decades ago, who suggested that one of the dissociated O atoms of O 2 sits at the bridge site and the other sits at a backbond of the Ge-Ge dimer [34,36]. However, the nondissociative O 2 adsorption has also been experimentally and theoretically proposed later in the literature [33,37,38]. Nevertheless, the established records fall short of experimental investigations on the interfacial electronic structure of Ge(001) with atomic O and molecular O 2 , especially at the embryonic stage of adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…8) Moreover, it was also claimed that dissociation of O 2 broke off the dimer bonds. 13) Nevertheless, reports in favor of nondissociative O 2 adsorption were predicted in theoretical calculations 12,16) and asserted by high-resolution electron energy loss spectroscopy (HREELS). 17) Until now, a microscopic view of the individual surface atom responding to oxygen could only be achieved in calculations to conform with scanning tunneling microscopy (STM) images.…”
mentioning
confidence: 99%
“…2. 12,13,15,16) The nondissociative model should be forsaken because it would result in only one GeO and one O 1s component. The existence of two GeO-related components may lead to immediate adoption of the FO model, which assigns the GeO(I) and GeO(II) components for the Ge atom at the top bridge site and the backbond of the surface dimer, respectively.…”
mentioning
confidence: 99%
“…Owing to the high carrier mobility and dopant solubility, germanium (Ge) has been regarded as one of the competing successors of silicon. The oxidation stages of Ge reconstruction surfaces had been well understood in the recent decade. Indeed, such knowledge provides great insight into developing the high-performance electronic devices on the Ge-based materials, e.g., high- k gate dielectric oxide layer on Ge(001), , and GeO 2 /Ge metal-oxide-semiconductor device with great electrical properties …”
Section: Introductionmentioning
confidence: 99%